Neurogenesis from Sox2 expressing cells in the adult cerebellar cortex - Thorn-Seshold, Julia; Wefers, Annika K. (Scientific reports, 2017)
We identified a rare undifferentiated cell population that is intermingled with the Bergmann glia of the adult murine cerebellar cortex, expresses the stem cell markers Sox2 and Nestin, and lacks markers of glial or neuronal differentiation. Interestingly, such Sox2+ S100− cells of the adult cerebellum expanded after adequate physiological stimuli in mice (exercise), and Sox2+ precursors acquired positivity for the neuronal marker NeuN over time and integrated into cellular networks. In human patients, SOX2+ S100− cells similarly increased in number after relevant pathological insults (infarcts), suggesting a similar expansion of cells that lack terminal glial differentiation.
Gesehen am 10.04.2018